A Conceptualized Model for Data Transmission in Underwater Acoustic Wireless Sensor Network - Agajo, James; Adewale, Ajao Lukman; Idama, Erhemwanahue O; Prudence, Ehizuenlen E; Felix, Ehigiator (Applications of Modelling and Simulation, 2020)
The complexity of underwater acoustic channel is considered to be quite possibly nature’s most unforgiving wireless medium. Nodes in underwater sensor networks which are used for oceanographic data collection, pollution monitoring, offshore exploration, tactical surveillance applications, and rapid environmental assessments are constrained by harsh physical environment. Also, data delivery schemes originally designed for terrestrial sensor networks are unsuitable for use in the underwater environment. Hence, this work investigates the development of an underwater transmission model by proposing a conceptualized Model for Data Transmission in Underwater Acoustic Wireless Sensor Network. The work assume that the noise power is the same for all the links. The work also assumes the channels are stable over each transmission frame. Without the relay nodes, the proposed mathematical model presents the minimum possible transmit power to achieve the required data rate between transmitting node and relay node. It evaluates the proposed model, after conducting several trials under different operating conditions using the data obtained. It then shows Throughput against Channel Bandwidth. Data transmission rate which can be measured from the graph shows an increase in channel bandwidth with decrease in throughput. Results show that at optimal power the proposed transmission model has significant advantages of improved performance and robustness over both the traditional direct transmission and the existing cooperative transmission schemes.